Proceedings of the 22nd International ACM SIGACCESS Conference on Computers and Accessibility 2020
DOI: 10.1145/3373625.3417012
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Creativity with a Comic Spin

Abstract: Creativity and humour allow people to be expressive and to address topics which they might otherwise avoid or fnd deeply uncomfortable. One such way to express these sentiments is via comics. Comics have a highly-visual format with relatively little language. They therefore ofer a promising opportunity for people who experience challenges with language to express creativity and humour. Most comic tools, however, are not accessible to people with language impairments. In this paper we describe Comic Spin, a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This work provides further evidence for more direct engagement and the co-design of human-centred high-tech AAC technologies directly with people living with CCNs. Much like previous research, employing people with aphasia as co-designers for insightful smartwatch AAC was successful [18,58,60,86]. Using guidelines such as those from Mack et al [48] to anticipate and adjust, ensured our participants felt empowered throughout the co-design process.…”
Section: Accessible Participatory Design Techniquesmentioning
confidence: 66%
See 1 more Smart Citation
“…This work provides further evidence for more direct engagement and the co-design of human-centred high-tech AAC technologies directly with people living with CCNs. Much like previous research, employing people with aphasia as co-designers for insightful smartwatch AAC was successful [18,58,60,86]. Using guidelines such as those from Mack et al [48] to anticipate and adjust, ensured our participants felt empowered throughout the co-design process.…”
Section: Accessible Participatory Design Techniquesmentioning
confidence: 66%
“…One researcher/SLT was assigned to each smaller group to support ideation of divergent solutions. Equivalently, previous co-design research by Neate et al [60,61,86] used low-fidelity tangible craft and paper-based wire-framing materials to successfully ideate with participants with aphasia. Amongst the smaller groups, the SLT/researcher would mediate discussions and appropriately use closed 'yes/no' questioning to support prototyping activities (e.g., drawing, writing and cutting) of a high-volume of participants' solutions.…”
Section: Co-design Workhop Two: Tangible Prototypingmentioning
confidence: 99%
“…Pressing "Save or Sharež will open the device's default share window, allowing users to save or share their comic strip to other applications. This version of Comic Spin was used in study 2 (reported in section 6) and difers from the version reported in [46] in several ways: it has a native save/share function, the user interface has been updated with larger images on the themes buttons, the buttons are screen-reader-friendly, it is responsive to screen size and additional non-verbal caption options such as "... ", "!!!" and "???"…”
Section: Comic Spinmentioning
confidence: 99%
“…Within this overarching paradigm, we followed a Design Thinking [14] process because of its focus on empathy and creative ideation. This process (empathize, deine, ideate, prototype and test) is described in detail in [46] and summarised here (Figure 3) along with key indings.…”
Section: Designing Comic Spinmentioning
confidence: 99%
See 1 more Smart Citation